Exploring Metaphors and Metaphorically Written Narratives in Student Teachers' Professional Identity Work - Gonny Schellings; Maaike Koopman; Douwe Beijaard (MDPI AG, 2024)
Metaphors can help student teachers to express what is essential in teachers' work and the process of learning to teach. This study reports on two types of metaphors generated and narrated by student teachers as part of their professional identity development during their internships. One type was about teaching their students (inside-classroom metaphor) and the other was about the student teachers' (broader) work context (out-of-classroom metaphor). In small groups, supervised by five teacher educators in total, they discussed each other's metaphors and accompanying narratives in order to gain (deeper) insight into their own and others' underlying beliefs and experiences. Metaphors and accompanying narratives of different cohorts of student teachers (n = 67 in total) were analyzed. The teacher educators were interviewed about their experiences with discussing the metaphors in small student teacher groups. The findings suggest that the student teachers confidently formulated metaphors and wrote accompanying narratives. They formulated quite a few standard metaphors that seemed very similar at first glance, but their underlying experiences and beliefs, conversely, showed many differences in nuance. Interviews with the teacher educators revealed that the discussions about the metaphors certainly led to new insights among the student teachers, such as thinking about their role as teachers, but the depth of the discussions was often limited. It can be concluded that engaging student teachers in using metaphors is certainly one way to become aware of, reflect on, and talk about one's (developing) professional identity, but it is important that adequate conditions are met, such as specific competencies teacher educators need for guiding this kind of identity work.